(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The missing piece. Advance Treatments Directives, medical activity and conscientious objection ABSTRACT: Law n. 219 of 2017 regulated Advance Treatment Arrangements by allowing the patient to express their treatment choices even for the future in the event of a supervening incapacity. The patient, therefore, may express prior consent or dissent with respect to future diagnostic-therapeutic options and/or individual medical treatments, including artificial hydration and/or nutrition practices. The paper examines the issue of the conflict of conscience of the physician called upon to carry out the patients decisions with the suspension or nonactivation of life-saving health treatments in the absence of a specific conscience clause regulated by law. A real missing piece. SOMMARIO: - PARTE PRIMA. Le Disposizioni Anticipate di Trattamento - 1. La legge sul consenso informato e sulle Disposizioni Anticipate di Trattamento (DAT): brevi cenni - 2. Le Disposizioni Anticipate di Trattamento (DAT): il quadro normativo - 3. Consenso informato, autodeterminazione terapeutica e Disposizioni Anticipate di Trattamento (DAT) - PARTE SECONDA. L’attività medica tra “scienza e coscienza” - 4. Profili giuridici e tendenze valoriali dell’obiezione di coscienza - 5. L’obiezione di coscienza tra tassatività e diretta azionabilità - 6. Personale medico e obiezione di coscienza tra le nuove frontier della medicina - 7. Il tassello mancante: l’assenza di una clausola di coscienza nella legge sulle DAT - 8. Conclusioni.